An Architecture for Automatic Load Distribution on Distributed Objects Computing Systems - Senger, Hermes; Sato, Líria Matsumoto (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
In this paper we propose an architecture for load distribution in distributed object computing systems. Our strategy implements load distribution both at request level and at object level. The load distribution mechanism is integrated at service level, and is based on system resources monitoring and application monitoring. Finally, we discuss some implementation aspects and show that the architecture may be used in DOC systems such as CORBA, DCOM and Java/RMI.